Patterns and universals of mate poaching across 53 nations: the effects of sex, culture, and personality on romantically attracting another person's partner - Schmitt, David P. (2004)
As part of the International Sexuality Description Project, 16,954 participants from 53 nations were administered an anonymous survey about experiences with romantic attraction. Mate poaching - romantically attracting someone who is already in a relationship - was most common in Southern Europe, South America, Western Europe, and Eastern Europe and was relatively infrequent in Africa, South/Southeast Asia, and East Asia. Evolutionary and social-role hypotheses received empirical support. Men were more likely than women to report having made and succumbed to short-term poaching across all regions, but differences between men and women were often smaller in more gender-egalitarian regions. People who try to steal another's mate possess similar personality traits across all regions, as do those who frequently receive and succumb to the poaching attempts by others. The authors conclude that human mate-poaching experiences are universally linked to sex, culture, and the robust influence of personal dispositions.